Recurring patterns in traditional Afghan settlements - Watts, Donald J. (My University, 2009)
This article investigates how traditional patterns of Afghan architecture may lend a culturally sensitive dimension to modern urban planning in Afghanistan. Case studies of traditional Afghan houses reveal common patterns of organization concerning building massing, thermal comfort, and the time and place of occupancy activities. Special attention is given to the method of growth through internal subdivision of traditional dwellings and the evidence of a limit as to minimal private open space versus enclosed space.
Keywords: Architecture; Afghanistan; Dwellings; Urban planning; Traditional houses